Shape design of magnetic circuit of the magnetic lens based on medial axis transform. (June 2021) - Chen, He; Dong, Quanlin; Liu, Xiaomeng; Li, Zhibing
Highlights: The mathematical model of magnetic circuit of magnetic lens is established. Based on the medial axis transform theory, the magnetic circuit shape of the magnetic lens is optimized. The optimized magnetic lens reflects better optical performance in the simulation results. The optimized magnetic lens the magnetic field near the pole piece is more concentrated, weakens the distribution of stray magnetic field and better focusing ability. Compared with the magnetic lens without optimized magnetic circuit structure, the optimized focusing ability can be improved by 10 %. Abstract: This paper proposes a method of designing a magnetic lens circuit based on axial transform theory. A unified mathematical description of the magnetic circuit profile is given within a medial axial transform in differential geometry. The objective constraint and geometric constraint equations of the magnetic circuit form a closed set of differential equations. Lastly, the optimized magnetic circuit is obtained using the solutions of the equations. The optical performance of the magnetic lens is significantly improved.